EVALUASI PROGRAM EKSTRAKURIKULER PRAMUKA DI SEKOLAH DASAR NEGERI SEGIRI 01 MENGGUNAKAN MODEL CONTEXT, INPUT, PROCESS, DAN PRODUCT - Setyowati, Erlin Tri; Agustina Tyas Asri Hardini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the Scout extracurricular program at SD Negeri Segiri 01 using the CIPP model (Context, Input, Process, Product). This study employed a qualitative approach with an evaluation research design. The subjects consisted of the principal, Scout instructors, and students in grades III–V. Data were collected through interviews, observations, and documentation. The results showed that the Context aspect was categorized as good because the program had clear objectives and was relevant to students' needs and the school's vision and mission. The Input aspect was categorized as good because it was supported by available human resources, facilities, and infrastructure. The Process aspect was categorized as fairly good because the activities were carried out according to the planned stages, although there were obstacles related to limited time, weather conditions, and some equipment. The Product aspect was categorized as good because the program positively contributed to students' discipline, responsibility, cooperation, independence, and self-confidence.